2020
DOI: 10.3390/jcm9123885
|View full text |Cite
|
Sign up to set email alerts
|

Could Periodontal Disease through Periopathogen Fusobacterium nucleatum Be an Aggravating Factor for Gastric Cancer?

Abstract: Periodontal disease affects the supporting tissues of the teeth, being a chronic inflammatory disease caused by specific microorganisms from subgingival biofilm. Fusobacterium nucleatum is a Gram-negative anaerobic bacterium that acts as a periodontal pathogen, being an important factor in linking Gram-positive and Gram-negative bacteria in the periodontal biofilm, but its involvement in systemic diseases has also been found. Several studies regarding the implication of Fusobacterium nucleatum in gastro-entero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 115 publications
0
10
0
1
Order By: Relevance
“…Additionally, Fusobacterium possesses adhesion and aggregation functions and can bind to most oral bacteria. 25 Fusobacterium can also adhere to some gut pathogenic bacteria, 26 which may disturb the gut microbiota, lead to intestinal inflammation, 27 , 28 and potentially serve as one of the biomarkers for detecting early intestinal bowel disease. 27 , 29 , 30 These results indicated that saliva-derived putative periodontopathic microbiota may enter the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Fusobacterium possesses adhesion and aggregation functions and can bind to most oral bacteria. 25 Fusobacterium can also adhere to some gut pathogenic bacteria, 26 which may disturb the gut microbiota, lead to intestinal inflammation, 27 , 28 and potentially serve as one of the biomarkers for detecting early intestinal bowel disease. 27 , 29 , 30 These results indicated that saliva-derived putative periodontopathic microbiota may enter the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Gingivitis is characterized by red, easily bled edematous gingiva and, if left untreated, the deeper periodontal tissues are implicated in the production of periodontitis that eventually ends in tooth loss [9]. Poor oral hygiene is created by local factors such as bacterial plaque and CALCULUS, which directly irritate periodontal tissues to cause periodontal diseases [10], [11]. Periodontal tissue is also directly affected by smoking and using tobacco products [5], [12], [15].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which F. nucleatum accelerates tumor progression and metastasis and induces tumor-chemoresistance have been thoroughly reviewed previously. [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] This paper focuses on fusobacterial mechanisms that guide tumor-specific colonization and protect tumors against anti-tumor immunity.…”
mentioning
confidence: 99%